Isolation and Screening of Amilolytic Bacteria Isolate from Cassava (Manihot utilissima) - Prapti Sedijani; Bq. Novi Aprilia; Dewa Ayu Citra Rasmi; Kusmiyati Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Amylase is an enzyme capable of hydrolyzing starch into simpler sugars. The use of amylase enzymes is urgently needed in various industrial fields, therefore the search for sources of amylase enzyme producers continues to be carried out for sources of amylase enzyme producers. Each industrial field has specific requirements for amylase enzymes. This study aims to isolate bacteria capable of producing amylase enzyme and to determine the amylase activity of bacteria isolated from cassava (Manihot utilissima) when incubated at different temperatures (room temperature and 30℃) and pH levels (7, 8, 9, and 10). The research involved bacterial isolation, testing the amylase activity of the isolated amylolytic bacteria at varying pH and temperatures, and characterizing the amylolytic bacteria. The amylolytic bacterial activity was qualitatively measured based on the clear zone's area formed around the colony. From this study 5 isolates showing amylolytic activity were obtained. The amylolytic activity index varied among the isolates, ranging from 0.12 to 0.59. The highest amylolytic activity index (0.59) was performed by S4 isolate on pH 10 medium incubated at 30℃. Microscopic and gram staining analysis suggest that two isolates were gram-negative coccus bacteria and three of them were gram-positive coccobaccilus bacteria.